Synthesis of nanoparticles in carbon arc: measurements and modeling. (9th May 2018) - Yatom, Shurik; Khrabry, Alexander; Mitrani, James; Khodak, Andrei; Kaganovich, Igor; Vekselman, Vladislav; Stratton, Brent; Raitses, Yevgeny
Abstract: Abstract : This work presents a study of the region of nanoparticle growth in an atmospheric pressure carbon arc. The nanoparticles are detected using the planar laser-induced incandescence technique. The measurements revealed large clouds of nanoparticles in the arc periphery bordering the region with a high density of diatomic carbon molecules. Two-dimensional computational fluid dynamic simulations of the arc combined with thermodynamic modeling show that this is due to the interplay of the condensation of carbon molecular species and the convection flow pattern. These results show that the nanoparticles are formed in the colder, peripheral regions of the arc and describe the parameters necessary for coagulation.